PENGARUH SIKAP DAN NORMA SUBJEKTIF TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KOTA AMBON - Angel Merlyn Pattimahu (P3M Politeknik Negeri Ambon, 2023)
This research that aims to find out: (1) The Influence of Attitudes towards Personal Taxpayer Compliance in ambon city (2) The Influence of Subjective Norms on Taxpayer Compliance of Private Individuals in Ambon city The population of this research is all taxpayers of private individuals registered in KPP Pratama Ambon. The sample used in this study was 78 respondents. Data collection method by questionnaire method. Validity test using total correlation, while reliability test using cronbach alpha. Classic assumption tests include normality tests, linearity tests, multicolinearity tests, and heterosesticity tests. The hypothesis test in this study used multiple regression analysis.The results of this study show that: (1) There is a positive and significant influence attitude towards the Compliance of Individual Taxpayers in Ambon City (2) There is a positive and significant influence of Subjective Norms on Taxpayer Compliance of Private Individuals in Ambon City Keywords: Attitudes, Subjective Norms, Personal Taxpayer Compliance in Ambon